Full 3D position reconstruction of a radioactive source based on a novel hyperbolic geometrical algorithm - Panaino, Costanza M.V.; Mackay, Ranald I.; Sotiropoulos, Marios; Kirkby, Karen J.; Taylor, Michael J. (Computer physics communications, 2020)
A new method to locate, with millimetre uncertainty, in 3D, a γ-ray source emitting multiple γ-rays in a cascade, employing conventional LaBr3(Ce) scintillation detectors, has been developed. Using 16 detectors in a symmetrical configuration the detector energy and time signals, resulting from the γ-ray interactions, are fed into a new source position reconstruction algorithm. The Monte-Carlo based Geant4 framework has been used to simulate the detector array and a 60Co source located at two positions within the spectrometer central volume. For a source located at (0,0,0) the algorithm reports X, Y, Z values of −0.3 ± 2.5, −0.4 ± 2.4, and −0.6 ± 2.5 mm, respectively. For a source located at (20,20,20) mm, with respect to the array centre, the algorithm reports X, Y, Z values of 20.2 ± 1.0, 20.2 ± 0.9, and 20.1 ± 1.2 mm. The resulting precision of the reconstruction means that this technique could find application in a number of areas including nuclear medicine, national security, radioactive waste assay and proton beam therapy.